Apparent reduced electric field control with nanosecond pulse width in a DC discharge for nitrogen vibrational excitation. (28th May 2019) - Kunishima, Yuki; Takashima, Keisuke; Kaneko, Toshiro
Abstract: A non-self-sustaining DC (NSS DC) discharge plasma source with an axial field geometry has been developed for emerging plasma applications on nitrogen fixation. This plasma source, composed of a pulse plasma generator and a DC power supply, enables external control of apparent reduced electric field ( E/N ). Pulse width extension, our proposed approach, is found to be a key parameter to achieve appropriate E/N for efficient nitrogen vibrational excitation leading to the nitrogen fixation processes. Owing to the pulse width modulation approach in the NSS DC discharge, the apparent E/N control up to 3 Td is achieved at 0.2 atm nitrogen.